Assessment of control and epidemiologic details of the schistosomiasis mansoni in Bananal, São Paulo, Brazil - Horacio Manuel Santana Teles; Cláudio Santos Ferreira; Maria Esther de Carvalho (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
The purpose of our study in the municipality of Bananal, state of São Paulo, Brazil, was to stop the transmission of schistosomiasis mansoni. Particular emphasis was given to such items as the active surveillance and eventual treatment of hosts, mapping parasite foci, and increasing the extent of basic sanitation in the municipality. Now, our records indicate that the eradication of schistosomiasis in the municipality of Bananal is attainable. However, as the vector Biomphalaria tenagophila can still be found in some water bodies within this municipality, it remains included in the area where schistosomiasis is endemic, which calls for very strict measures to avoid the human cases of schistososomiasis. The expansion of the coverage of the basic sanitation network and treatment of Schistosoma mansoni cases diagnosed during periodic surveys are part of the plans to eradicate schistosomiasis in Bananal.